A new approach on electromagnetism with dual number coefficient octonion algebra - Chanyal, Bhupesh Chandra; Chanyal, Sunil Kumar; Bektas, Ozcan; Yuce, Salim (WORLD SCIENTIFIC PUBL CO PTE LTD, 2016)
Dual number coefficient octonion (DNCO) is one of the kind of octonion, it has 16 components with an additional dual unit epsilon. Starting with DNCO algebra, we develop the generalized electromagnetic field equations of dyons regarding the DNCOS spaces, which has two octonionic space-times namely the octonionic internal space-time and the octonionic external space-time. Besides, the generalized four-potential components of dyons have been expressed with respect to the dual octonion form. Furthermore, we obtain the symmetrical form of Dirac-Maxwell equations, and the generalized potential wave equations for dyons in terms of the dual octonion. Finally, we conclude that dual octonion formulation is compact and simpler like octonion formulation.
Keywords: Octonion; dual octonion; dyons; Dirac-Maxwell's equations; potential wave equations; Physics